Pengembangan E-LKPD dengan Pendekatan Saintifik terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas V - Agustin, Audia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to develop E-LKPD with a scientific approach to the learning outcomes of Pancasila education for grade V of SD Negeri 59 Lubuklinggau. The type of development used is the 4D model development (four-D model). Based on the results of research and development, shows that the development of E-LKPD with a scientific approach to Pancasila education learning for grade V of SD Negeri 53 Lubuklinggau is valid and practical. The validity of E-LKPD is shown through the results of expert validation including media experts, language experts, and material experts. Based on the validation results, it is known that E-LKPD with a scientific approach is categorized as quite good with a validity percentage of 0.76 so E-LKPD on the NKRI material is classified as quite valid. The practicality of E-LKPD is measured through a questionnaire obtained by a small group trial involving 6 students and 1 teacher categorized as very practical with a percentage of 86.30% with a high effectiveness value. The number of values ​​that have been summarized from the assessment is 0.68 which is categorized as moderate. Conclusion, that the development of E-LKPD with a scientific approach can improve student learning outcomes in Pancasila education Keywords: E-LKPD, Scientific & Learning Outcomes